Estimation of long-term costs of postacute care in survivors of the methanol poisoning outbreak - Barták, Miroslav; Rogalewicz, Vladimír; Doubek, Jaroslav; Šejvl, Jaroslav; Petruželka, Benjamin; Zakharov, Sergey; Miovský, Michal (BMJ open, 2021)
OBJECTIVES: To fill the existing research gap related to long-term costs of postacute care in methanol poisoning survivors, healthcare cost for 6 years after the outbreak has been modelled and estimated. DESIGN: In a prospective longitudinal cohort study, data collected from 55 survivors of the Czech methanol mass poisoning outbreak in 2012 were collected in four rounds (5 months, then 2, 4 and 6 years after the discharge) in the General University Hospital in Prague according to the same predefined study protocol. The collected data were used to inform the cost model. SETTING AND PARTICIPANTS: All 83 patients discharged from a hospital poisoning treatment after the 2012 methanol outbreak were informed about the study and invited to participate. Fifty-five patients (66%) gave their written informed consent and were followed until their death or the last follow-up 6 years later. The costs were modelled from the Czech healthcare service (general health insurance) perspective. MAIN OUTCOME MEASURES: Long-term national budget impact of the methanol poisoning outbreak, frequencies of sequelae and their average costs. RESULTS: The postacute cost analysis concentrated on visual and neurological sequelae that were shown to be dominant. Collected data were used to create process maps portraying gradual changes in long-term sequelae over time. Individual process maps were created for the central nervous system, peripheral nervous system, sequelae detected during eye examinations and sequelae concerning the visual evoked potentials. Based on the process maps the costs of the postacute outpatient care were estimated. CONCLUSIONS: In 2013-2019 the highest costs per patient related to postacute care were found in the first year; the average costs decreased afterwards, and remained almost constant for the rest of the studied period of time. These costs per patient ranged from CZK4142 in 2013 to CZK1845 in 2018, when they raised to CZK2519 in 2019 again.
Keywords: Evoked Potentials, Visual; přežívající; methanol; zrakové evokované potenciály; longitudinální studie; otrava; Subacute Care; náklady na zdravotní péči; subakutní péče; Prospective Studies; Survivors; Methanol; lidé; Humans; Health Care Costs; epidemický výskyt choroby; Poisoning; Longitudinal Studies; Disease Outbreaks; prospektivní studie